Prevalence of gender-based violence and factors associated with help-seeking among university students in sub-Saharan Africa - Ruth Owusu-Antwi; Lisa Fedina; Maria Jose Baeza Robba; Kristie Khatibi; Dennis Bosomtwe; Etienne Nsereko; Oluwatobiloba Shadare; Sarah Compton; Akanni Akinyemi; Moreoagae Bertha Randa; Abiola A Afolabi; Michelle L. Munro-Kramer (Women's Health)
Background: Gender-based violence (GBV) is a global public health problem. While research exists on GBV and associated help-seeking behaviors among university students, few studies have assessed the prevalence of GBV, including experiences and barriers to help-seeking, within sub-Saharan African university settings. Objectives: The objective of this study was to examine the prevalence of GBV victimization among university students in six sub-Saharan African countries and describe experiences of formal and informal help-seeking among students who self-identified as victims of GBV since attending university. Design: An online, cross-sectional survey study was administered to university students from July to October 2023 at nine participating universities in sub-Saharan Africa. Methods: Descriptive statistics were used to describe types of violence experienced among students ( N  = 2249). Bivariate analyses ( t -tests, chi-square) and multivariate logistic regressions were used to examine demographic factors associated with formal and informal help-seeking behavior among a sub-sample of GBV victims ( n  = 298). Results: Among the 2249 sample of students, the prevalence of physical violence was 30.9%, 18.7% for sexual violence, 64.9% for psychological violence, and 63.7% for stalking. Among a sub-sample of GBV victims ( n  = 298), most (78.2%) sought informal help from friends, partners, or family members and less than one-third (29.5%) sought help from formal sources (e.g., university administrators, police). Logistic regression results indicated that university country was associated with formal help-seeking; that is, students in Ghana and Rwanda were over twice as likely to seek formal help than students in Nigeria (odds ratio (OR) = 2.58, 95% confidence interval (CI): 1.38–4.85, p  < 0.01; OR = 2.62, 95% CI: 1.20–5.71, p  < 0.05, respectively). While differences by gender were noted in formal help-seeking behavior at the bivariate level, gender was not associated with formal help-seeking after adjusting for GBV training and other demographics. Conclusion: GBV is a significant public health issue among university students in sub-Saharan Africa. University policies and prevention programs are needed to reduce GBV and increase the capacity of formal sources to effectively respond to GBV.